2020
DOI: 10.1038/s41467-020-19376-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the mechanism of rhodopsin phosphodiesterase

Abstract: Rhodopsin phosphodiesterase (Rh-PDE) is an enzyme rhodopsin belonging to a recently discovered class of microbial rhodopsins with light-dependent enzymatic activity. Rh-PDE consists of the N-terminal rhodopsin domain and C-terminal phosphodiesterase (PDE) domain, connected by 76-residue linker, and hydrolyzes both cAMP and cGMP in a light-dependent manner. Thus, Rh-PDE has potential for the optogenetic manipulation of cyclic nucleotide concentrations, as a complementary tool to rhodopsin guanylyl cyclase and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…As previously described ( 40 ), the protein was crystallized in lipidic cubic phase (LCP). The protein was reconstituted into monoolein at a weight ratio of 1:1.5 (protein:lipid).…”
Section: Methodsmentioning
confidence: 99%
“…As previously described ( 40 ), the protein was crystallized in lipidic cubic phase (LCP). The protein was reconstituted into monoolein at a weight ratio of 1:1.5 (protein:lipid).…”
Section: Methodsmentioning
confidence: 99%
“…The rhodopsin proteorhodopsin and related proteins have aroused continuous and extensive interest both experimentally and theoretically among researchers, especially during the past 20 years [ 1 , 2 , 3 , 4 , 5 ]. Rhodopsin is a seven transmembrane α-helices (TM) protein which uses retinal as a chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…The results achieved by ZOO have successfully proven the effectiveness of SWSX in the structural analysis of various samples at SPring-8 (Taniguchi et al, 2017;Kato et al, 2018;Shihoya et al, 2018;Liu et al, 2019;Ikuta et al, 2020;Jiang et al, 2020;Shiimura et al, 2020;Umeda et al, 2020;Yu et al, 2020). In these studies, hierarchical clustering was shown to be essential to select homogeneous sub-datasets to be merged.…”
Section: Introductionmentioning
confidence: 87%